Trade or migration? A Study of red-black burnished ware at Tell Qarqur, Syria - Kaercher, Kyra Elise (My University, 2010)
Both trade and migration have been used by archaeologists to explain change in material culture. In particular, archaeologists have interpreted changes in the types of ceramics recovered at archaeological sites as evidence of either regional trade and/or the migration of people into the area. The appearance of one particular ceramic type, Red-Black Burnished Ware (RBBW) in the Ancient Near East circa 2500 B.C. has been explained as resulting from either trade or the migration of people. RBBW is distinct from the local wares, but appears similar to ceramics found in Transcaucasia (present day Republic of Georgia) (Rothman 2002). One site at which RBBW is found is the site of Tell Qarqur, Syria. This paper will examine the forms of pottery vessels recovered at Tell Qarqur to determine their function in order to demonstrate whether the occurrence of this pottery at the site can be attributed to trade or migration.
Keywords: Ceramics -- Syria -- Qarqur, Tall -- History.; Pottery -- Syria -- Qarqur, Tall -- History.; Qarqur, Tall (Syria) -- Commerce -- History